PENGEMBANGAN SISTEM PENYEDIAAN AIR MINUM PERPIPAAN PDAM UNIT PASAR KUOK KECAMATAN BATANG KAPAS KABUPATEN PESISIR SELATAN - Slamet Raharjo; Aulia Azhar; Chairil Syam (Badan Penelitian and Pengembangan (Balitbang), Padang, West Sumatra, Indonesia, 2016)
Batang Kapas District is a developing area in Pesisir Selatan Regency which requires reliable water supply system. Currently, the district has a level of water supply system of only 15.74% in which some of the facilities are broken due to 2009 earthquake. According to MDG’s, the district must develop pipeline system of water supply. The development is carried out for Nagari IV Koto Mudiak dan Nagari IV Koto Hilie. Design period is for 17 years (2013-2030) to achieve a service level of 34 %. The target capacity is 16 l/det, using Batang Tuik river as the water source. The water supply system includes channel intake, transmission pipe, water treatment plant (WTP), distribution reservoar, and distribution pipe. Transmission pipe is GIP DN 150 mm (333,75 m). WTP includes Pra-sedimentation, rapid sand filter, and disinfection. Distribution system uses gravitational branch pattern. Distribution pipe includes GIP DN 300 mm (1.329,2 m), DN 250 mm (5.409,3 m), DN 150 mm (3.302,7 m), PVC DN 50 mm (2.387 m), and reservoar with capacity of 277 m3.